The Innovation Strategy and Effects in Organizational Learning: The Manufacturing Sector in Colombia - Vélez Osorio, Iris María (2018)
Purpose To understand how innovation strategy measure by organizational methods and technology equipment, affects to organizational learning measure by improvement in production, distribution and logistics systems. MethodologyThis is an empirical analysis of the innovation strategy and organizational learning, concentrating on 8835 manufacturing companies in 33 subsectors with innovative processes, investment in research and development, better organizational methods and technology equipment, using databases from the National Department of Statistics-DANE. Multiple Regression. Software SPSS. Findings: An industry with an innovation strategy tends to get better and improved processes, and this learning allows firms to achieve value creation for the customer, turning into better types of products offered with unique characteristics to compete in the challenging markets. Where the greatest improvement in methods of production, distribution, delivery and logistics will be the result of a very well manage innovation, to more innovation strategy more organizational learning. Research Limitations:The type of innovations in process were heterogeneous and the data do not allow to clarify specific improvement and innovation type. Practical Implications:This empirical study establishes, two special practical implications, first identify special characteristics in innovation in one of the most representative sectors of the Colombian economy that even though address incremental innovations, especially through processes, and the second element is to recognize that the innovative strategy becomes a differentiating factor for companies in this sector, beyond technological barriers and culture of innovation that may appear. Originality:The research was made for the most innovative sectors in the manufacturing Colombian industry, this particular context was not studied enough before in the particular constructs of innovation strategy and organizational learning. Key Words: Innovation, manufacturing industry, strategy, organizational learning, processes.JEL: M1, M10